2019
DOI: 10.1002/mrd.23135
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of complex coordinated molecular signaling by 5HT and a cocktail of inhibitors leads to ovarian maturation of Penaeus monodon in captivity

Abstract: In aquaculture practices, prawn cultivation holds the major share and Penaeus monodon is the main species cultured. The decline in production of P. monodon is mainly due to the limited availability of domesticated broodstock, which is attributed to its reproductive cycle, controlled by complex coordinated signaling mechanisms. Unilateral eyestalk ablation of domesticated females held in captivity is done to induce ovary development, which has certain disadvantages, including a high rate of mortality. Thus, dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…This induction was further confirmed by treating with CrzR dsRNA, which might suggest an integrative role of Crz signaling during ovarian development. Moreover, this result conforms to the properties of CrzR as a GPCR, as in many studies, the intracellular cAMP level plays pivotal roles in regulating the expression of Vg, cyclinB, and Cdc2 Mani et al, 2019;Feng et al, 2021;Wan et al, 2022).…”
Section: B a Figuresupporting
confidence: 87%
“…This induction was further confirmed by treating with CrzR dsRNA, which might suggest an integrative role of Crz signaling during ovarian development. Moreover, this result conforms to the properties of CrzR as a GPCR, as in many studies, the intracellular cAMP level plays pivotal roles in regulating the expression of Vg, cyclinB, and Cdc2 Mani et al, 2019;Feng et al, 2021;Wan et al, 2022).…”
Section: B a Figuresupporting
confidence: 87%
“…Previous studies showed that eyestalk ablation had the ability to promote gonad maturation and reproduction in female crustaceans, which disturbed the process of synthesis and release of gonad inhibiting hormone (Mani et al, 2019). Here, expression of CqFtz‐f1 mRNA after eyestalk ablation was measured, and we found that CqFtz‐f1 expression was increased significantly at 24 and 96 h compared with the control group.…”
Section: Discussionmentioning
confidence: 99%